A lab-scale heliostat positioning control using fuzzy logic based stepper motor drive with micro step and multi-frequency mode - Jirasuwankul, N.; Manop, C. (My University, 2017)
This paper proposes positioning control technique for a lab-scale heliostat by application of hybrid stepper motors and fuzzy logic controllers. Steady state tracking error has been kept minimal by micro step drive together with speed control by multi stepping rate adjustment. By supportive video streaming device and image processing, a reflected image of illuminant area on the target is captured and analyzed, an obtaining position error in azimuth and altitude angles are real-time fed to the fuzzy controllers. As a result, the closed loop tracking is formulated and steady state error can then be minimized. Simulation and experimental results confirm the proposed technique.
Keywords: Fuzzy logic; Heliostat; Image processing; Micro step; Stepper motor